2014
DOI: 10.1136/bmjopen-2014-006058
|View full text |Cite
|
Sign up to set email alerts
|

Can the painDETECT Questionnaire score and MRI help predict treatment outcome in rheumatoid arthritis: protocol for the Frederiksberg hospital's Rheumatoid Arthritis, pain assessment and Medical Evaluation (FRAME-cohort) study

Abstract: Introduction Pain in rheumatoid arthritis (RA) is traditionally considered to be of inflammatory origin. Despite better control of inflammation, some patients still report pain as a significant concern, even when being in clinical remission. This suggests that RA may prompt central sensitisation—one aspect of chronic pain. In contrast, other patients report good treatment response, although imaging shows signs of inflammation, which could indicate a possible enhancement of descending pain inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
0
15
0
3
Order By: Relevance
“…Rifbjerg-Madsen et al [29] reported that non-nociceptive pain was very common in RA and was associated with higher scores of disease activity. A recently published study that assessed the NeP component in RA by the PainDetect questionnaire showed that medium and higher scores of NeP had poorer effects on depression, anxiety, fatigue, pain, and the mental component of HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Rifbjerg-Madsen et al [29] reported that non-nociceptive pain was very common in RA and was associated with higher scores of disease activity. A recently published study that assessed the NeP component in RA by the PainDetect questionnaire showed that medium and higher scores of NeP had poorer effects on depression, anxiety, fatigue, pain, and the mental component of HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Она ассоциируется со слабой активностью воспаления, о чем свидетельствуют низкие исходные уровни СОЭ и С-реактивного белка (СРБ) [96]. Более того, при наличии признаков центральной сенситизации (счет >19 по опроснику PainDETECT) прогнозируются негативные результаты терапии, оцениваемой по DAS28-СРБ [97]. С помощью определения экспрессии генов можно идентифицировать причины боли у отдельных больных РА на молекулярном уровне.…”
Section: прогнозирование остаточной боли после терапии раunclassified
“…Сохраняющаяся боль, несмотря на положительный клинический ответ, тесно связана с функциональной слабостью и инвалидностью [71], фибромиалгией [92] и слабой активностью воспаления, о чем свидетельствуют низкие уровни скорости оседания эритроцитов (СОЭ) и С-реактивного белка предшествующие терапии [93]. Более того, при уровнях показателя по опроснику, указывающему на центральную сенситизацию -PainDETECT превышающих 19, прогнозируются негативные результаты терапии, оцениваемой по клиническому показателю активности заболевания (DAS28-CRP) [94].…”
Section: прогнозирование остаточной боли после терапииunclassified